Visual evoked potentials in neuromyelitis optica and its spectrum disorders: $hMarius Ringelstein, Ingo Kleiter, Ilya Ayzenberg, Nadja Borisow, Friedemann Paul, Klemens Ruprecht, Markus Kraemer, Eva Cohn, Brigitte Wildemann, Sven Jarius, Hans-Peter Hartung, Orhan Aktas, Philipp Albrecht - Ringelstein, Marius; Kleiter, Ingo; Ayzenberg, Ilya; Borisow, Nadja; Paul, Friedemann; Ruprecht, Klemens; Kraemer, Markus; Cohn, Eva; Wildemann, Brigitte; Jarius, Sven; Hartung, Hans-Peter; Aktas, Orhan; et al. (Multiple sclerosis journal, 2014)
Optic neuritis (ON) is a key feature of neuromyelitis optica (NMO). Recently, NMO patients of predominantly Afro-Brazilian origin were evaluated by visual evoke...
First published September 5, 2013
Gesehen am 22.09.2020